The Teacher Community Role toward Teacher Professionalism on Designing EFL Instructional Objectives - Hafiz Nurulhaq, Gulam; Kurniawan, Eri; Hikmawan, Ihsan; Ginanjar, Regiana; Firman (Institut Agama Islam Negeri Parepare, 2024)
Developing professional competence is always required by the teacher to present meaningful learning experiences to reach the goal. Moreover, the pandemic has changed every side of life, including teaching and learning activities. One of the competencies is designing the instructional objectives, and the teacher community can support their development. This study explores the role of the teacher's community in developing teachers' professional competence in designing the instructional objective in the EFL context. This study uses qualitative methods with questionnaires and interview instruments to collect the data. Two teachers contribute to this study. They come from senior high school teachers. One teacher teaches in a public school, and the other teaches in a private one. The result showed that three types of teachers' communities play a role in respondents' development in teachers' professional competence in designing instructional learning objectives. Besides, they can design the learning objectives; further researchers may conduct follow-up research with a broader subject, complete literature, and more relevant methods to draw generalizations.